Immune responses in healthy adults elicited by a bivalent norovirus vaccine candidate composed of GI.4 and GII.4 VLPs without adjuvant - Waerlop, Gwenn; Janssens, Yorick; Jacobs, Bart; Jarczowski, Franziska; Diessner, André; Leroux-Roels, Geert; Klimyuk, Victor; Leroux-Roels, Isabel; Thieme, Frank (Frontiers in Immunology, 2023)
The development of an efficacious vaccine against norovirus is of paramount importance given its potential to reduce the global burden of norovirus-associated morbidity and mortality. Here, we report a detailed immunological analysis of a phase I, double-blind, placebo-controlled clinical trial performed on 60 healthy adults, ages 18 to 40. Total serum immunoglobulin and serum IgA against vaccine strains and cross-reactive serum IgG against non-vaccine strains were measured by enzyme immunoassays, whereas cell-mediated immune responses were quantified using intracellular cytokine staining by flow cytometry. A significant increase in humoral and cellular responses, e.g., IgA and CD4+ polypositive T cells, was triggered by the GI.4 Chiba 407 (1987) and GII.4 Aomori 2 (2006) VLP-based norovirus vaccine candidate rNV-2v, which is formulated without adjuvant. No booster effect was observed after the second administration in the pre-exposed adult study population. Furthermore, a cross-reactive immune response was elicited, as shown by IgG titers against GI.3 (2002), GII.2 OC08154 (2008), GII.4 (1999), GII.4 Sydney (2012), GII.4 Washington (2018), GII.6 Maryland (2018), and GII.17 Kawasaki 308 (2015). Due to viral infection via mucosal gut tissue and the high variety of potentially relevant norovirus strains, a focus should be on IgA and cross-protective humoral and cell-mediated responses in the development of a broadly protective, multi-valent norovirus vaccine. Clinical trial registration https://clinicaltrials.gov, identifier NCT05508178. EudraCT number: 2019-003226-25.